Microbiological dynamics of different poultry waste disposal methods - GURPREET KAUR; DALJEET KAUR; PAVITER KAUR; NEEMISHA; SANDEEP UNIYAL; YASHPAL SINGH; D S MALIK (Indian Journal of Animal Sciences)
The improper handling and disposal of animal excrement, especially that from chickens and other animals, has historically resulted in serious environmental and societal difficulties. This research study outlines the method for improving the usage of rotational compost bins in the disposal of poultry waste. The objective was to study the microbiological dynamics of different poultry waste disposal methods. Fresh poultry manure, together with dead bird carcasses and paddy straw (i.e. aerobic composting-T1 group) was composted and compared to T2 group in which additionally yeast was incorporated @7.5%. Keeping moisture at 45-50%, the initial C:N ratio was set at 30:1 in both treatment groups and the study was carried for 90 days. The effect of introducing yeast probiotic (T2-probiotic consortium assisted aerobic composting) on compost temperature, odour and structure was assessed and their impact on total microbial load and actinomycetes were compared to that of T1 group. The decrease in total bacterial count varied non significantly in both the treatment groups with initial decline in number in group T2 as compared with T1. The E. coli count of the composting material varied non significantly at both initial and final stage of composting. The number of fungal colonies in T1 and T2 did not differ significantly initially but significant difference was observed in later stages. The actinomycetes colonies start developing towards the last phase of composting period in both groups and differ significantly. The quality of the manure compost was evaluated at various phases of operation. Inoculating yeast as a probiotic into the composting process increased the quality of the compost, transforming it into a stable and odor-free finished compost.